Postoperative Wound Care Regimen in Open Septorhinoplasty - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
The many benefits of the open-approach septorhinoplasty should not be excluded on the basis of columellar scarring alone. Technical factors that contributed to the favorable outcome of the columellar scar included proper planning of location and design of the incision used, meticulous closure, and good postoperative care. In the current study, we describe a simple postoperative wound care procedure that allows clean visualized wound with less crust formation, easy removal of the sutures by the surgeon, and better columellar scar in the early postoperative period.
Keywords: Columellar incision; columellar scar; hydrogen peroxide; OPEN RHINOPLASTY; SCAR ANALYSIS; INCISION; CREAM; EMLA